RANCANG BANGUN SOLAR TRACKING SYSTEM BERBASIS ESP UNTUK OPTIMALISASI PENYERAPAN ENERGI MATAHARI PADA SOLAR PANEL - Mochammad Yusuf Habiburrahman; n/a Nurussa’adah; Akhmad Zainuri (Jurnal Mahasiswa TEUB, 2023)
Electricity is one of the main supporting factors for human life. Most of the sources of electrical energy in Indonesia are produced from fossil energy. This is what encourages the use of alternative energy because fossil fuels are non-renewable and are produced over a very long time. One alternative energy that has considerable potential in Indonesia is Solar Power Plants (PLTS).Effectiveness is one of the main factors in the problem, this is because the angle of the sun is always changing every time making the intensity level of the sun and the angle of inclination of the sun's light on the solar panels not maximum. For now, there is still a lot of static use of solar panels so they don't produce optimum power. Therefore, we need a system that can help solar panels always get the maximum intensity of sunlight and be perpendicular to the direction of sunlight. In this research, a system design is carried out using sensors and actuators and aims to help solar panels track the position of the sun, which is called a solar tracking system. Keywords: ESP, Solar panel, Tracking system REFERENSIHuang, Y.J., Kuo, T.C., Chen, C.Y., Chang, C.H., Wu, P.C., dan Wu, T.H. (2009). The Design and Implementation of a Solar Tracking Generating Power System, Engineering Letters, 17:4. EL_17_4_06, Advance Online Publication.Priatman, J. (2000). Perspektif Arsitektur Surya Di Indonesia, Dimensi Teknik Arsitektur, Universitas Kristen Petra, Surabaya.Magga, R., Mustofa, dan Arifin, Y. (2015). Desain Hybrid Panel Surya Tipe Monocrystalline Dan Thermal Kolektor Fluida Air. Jurnal IPTEK. 19(2):67–74Hikmawan, S.R. & Suprayitno, E.A. (2018). Rancang Bangun Lampu Penerangan Jalan Umum (PJU) Menggunakan Soar Panel Berbasis Android. ELINVO (Electronics, Informatics, and Vocational Education), 9-10.